Arbitrage Opportunity for Exchange Traded Funds (ETFs) in the Indian Stock Market - An Empirical Analysis - Dharani, M.; Natarajan, P. (Indian Journal of Finance, 2011)
Exchange-traded funds (ETFs) are generally index-based funds that allow investors to buy or sell exposures to an index through a single financial instrument. ETF units are created and redeemed in-kind, rather than in-cash (as in the case of a unit trust fund). The in-kind creation and redemption mechanism allows arbitrage opportunities whenever unit prices deviate from the value of the underlying portfolio. The main objective of this study is to examine the arbitrage opportunity available to the retail and institutional investors in the newly traded financial instrument called as Exchange Traded Funds. The study employs the simple regression, multiple regressions and auto regression to achieve the objective of the study for the sample ETFs from an inception date to 31st December 2009. The results of the study show that sample ETFs, except Kodak PSU Bank ETFs are traded at a discount in the Indian stock market. The study advises the retail and institutional investors to buy the Nifty BeES, Nifty Junior BeES, Bank BeES, Shariah BeES, Kodak PSU Bank ETFs, Reliance Bank ETFs, Q Nifty and UTI SUNDER from stock exchanges and sell them in fund houses. They may also buy the PSU Bank BeES from the fund houses and sell it to the secondary market. Finally, this study concludes that premium or discount of the Bank BeES, Shariah BeES, and Kodak PSU Bank ETF vanishes within a day, whereas six premiums or discounts of the remaining ETFs continue to exist in the following days, which also shows more arbitrage potential.